Longitudinal assessment of quality of life in indolent non-Hodgkin lymphomas managed with active surveillance. Issue 14 (6th December 2022) - Major, Ajay; Wright, Rachel; Hlubocky, Fay J.; Smith, Sonali M.; Prochaska, Micah T.
Abstract: There are limited data describing the impact of active surveillance on longitudinal health-related quality of life (HRQoL) in patients with indolent non-Hodgkin lymphomas (NHL). A cohort of untreated indolent NHL patients completed FACT-LYM questionnaires at 6, 12, 18, 24, and 36 months after diagnosis. Longitudinal FACT-LYM scores were analyzed by ANOVA and generalized linear mixed models. Indolent NHL scores were compared to norm general population scores. A total of 52 patients were identified, of which 46 (88%) remained on active surveillance at 36 months. There was no significant change in any of the FACT-LYM scores over 36 months. As compared to the general population, indolent NHL patients had higher, clinically meaningful scores in physical, functional, and social well-being, but not emotional well-being. Patients with indolent NHL on active surveillance have globally preserved HRQoL for up to 3 years after diagnosis. Emotional well-being continues to be an unmet need during active surveillance.